Laurie Armato plays mandolin and Pinu Baldacchino plays guitar in the Manuel Casha Maltese folklore music project. - Armato, Laurie; Baldacchino, Pinu (1991)
Folkloric recording.
Recorded during 1991 in Donvale, Victoria.
Digital master available
Songs performed in Maltese.
Summary not yet available.
Keywords: Maltese Australians -- Music; Guitar and mandolin music